(3TQM GdQVi Ydi ebOeI GHf GdMGLH aj GdfMhs - (3fLe GdOjf QVi GdOjf eMeO Hf GdMSf GdCSJQGHGPi GdfMhis; (3GHf GdMGLH , LeGd GdOjf CHh YeQh GHf GdMGLH, LeGd GdOjf CHh YeQh GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3hHYO abO WdH Edi HYV ef GYJfi HUdGM MGdI hGSYaI eeG JSYg HbOQJi ef ebJQMGJ s
(3BNQgG (B:s
(3dchf GdJfhjf dGReI EPG de jcf eGfY acGfgG KGHJg GjVkG eY YQhV GdMPa gPG BNQ TQM GdebOeI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs